“Sente o negro drama”: emparedamento, uma expressão subjetiva do racismo - Pereira, Juliano Baltazar (2025)
The present study investigates the subjective dimension of a particular contradiction experienced by a segment of the Black Brazilian population that has undergone some degree of social mobility in the contemporary context. The research is grounded in Cultural-Historical Psychology and employs historical-dialectical materialism as its method. The work is structured into two parts. Initially, it approaches an exploratory review, selecting studies on racial relations and human development. This review emphasizes the historical trajectory of racial issues in Brazil and their contemporary articulation with neoliberalism and the expansion of a "Black middle class.". Subsequently , the study draws on two types of empirical materials: rap and funk lyrics, and clinical vignettes derived from the author's psychotherapeutic practice, which illustrate the subjective conflicts of Black individuals associated with what is termed "emparedamento" (a state of confinement). The results indicate that the internalization of racism structures the psychological dynamics of these individuals, potentially leading to what we define as "emparedamento": an experience of isolation and division between the new social position achieved and the identity identity shaped by their previous class and racial condition. This phenomenon is a consequence of structural contradictions, but also manifests as an internal conflict, wherein individuals feel displaced both in their new social environments and in relation to their community of origin. The study seeks to broaden the discussion on the impact of racism on the subjectivity of Black individuals undergoing social mobility and to contribute to Critical and Social Psychology in Brazil